UWB bandpass filter using dual stepped impedance stub loaded resonators. Issue 2 (February 2014) - Oh, Sangyeol; Shin, Beomsoo; Jeong, Jichai; Kim, Young‐Sik; Lee, Jaehoon
ABSTRACT In this article, a new ultrawideband (UWB) bandpass filter is proposed, with dual stepped‐impedance stub‐loaded resonators (SISLRs). As the proposed filter can provide the better in‐band performance due to the dual SISLRs, it was possible to design this UWB filter without apertures in the ground plane. The passband performance of the proposed filter is superior to that of the conventional filter based on a single SISLR with aperture‐backed interdigital coupled‐lines, while the resonant frequencies and sharp rejection skirt characteristics of the conventional filter are retained without apertures in the ground plane. The performance of the new filter was confirmed by simulation with a full‐wave electromagnetic simulator and by actual implementation and measurement. The passband of the implemented filter covers the range of 3.24∼11.03 GHz. The group delay is less than 0.5 ns and flat in the passband, and sharp attenuations appear near the passband. © 2014 Wiley Periodicals, Inc. Microwave Opt Technol Lett 56:448–450, 2014